2014
DOI: 10.1089/ten.tea.2013.0279
|View full text |Cite
|
Sign up to set email alerts
|

Biological Evaluation of Human Degenerated Nucleus Pulposus Cells in Functionalized Self-Assembling Peptide Nanofiber Hydrogel Scaffold

Abstract: Nucleus pulposus (NP) tissue engineering has been proposed as a novel biological treatment for early-stage intervertebral disc degeneration. In this study, a novel functional self-assembling peptide PKP was first designed by linking the short functional motif of bone morphogenetic protein-7 (BMP7) to the C-terminal of RADA16-I, and another new functional self-assembling peptide was obtained by mixing RKP with RADA16-I. Then, the biocompatibilities and bioactivities of RKP and RAD-RKP for human degenerated nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 47 publications
1
28
0
Order By: Relevance
“…Total RNA was extracted from cells/scaffold, using TRIzol (Invitrogen) according to the manufacturer's instructions . The RNA concentration was determined by spectrophotometry and RNA was reverse‐transcribed with PrimeScript™ RT Master Mix (TaKaRa, China).…”
Section: Methodssupporting
confidence: 58%
See 2 more Smart Citations
“…Total RNA was extracted from cells/scaffold, using TRIzol (Invitrogen) according to the manufacturer's instructions . The RNA concentration was determined by spectrophotometry and RNA was reverse‐transcribed with PrimeScript™ RT Master Mix (TaKaRa, China).…”
Section: Methodssupporting
confidence: 58%
“…Our previous studies reported a novel type of functional self‐assembling peptide (RADA‐KPSS) constructed by conjugating short functional motifs of BMP7 (KPSS) to the C‐terminus of the RADA16‐I. It displays three benefits: good biocompatibility, excellent bioactivity, and injectability . Furthermore, we demonstrated that the RADA‐KPSS peptide enhanced NPC proliferation and ECM synthesis in physiological conditions .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 Only when KPS was mixed with RADA16-I at an equal volume ratio (RAD-KPS) were the β-sheet structures regained. Furthermore, our previous study also showed that RAD-KPS was more suitable for NP tissue engineering applications than was pure RKP.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 BMP7 not only stimulated nucleus pulposus cells to secrete aggrecan and collagen II in vitro but also prevented disc degeneration in vivo. 31 35 we successful conjugated one important short peptide, KPS, to the C-terminus of RADA16-I to obtain a novel functionalized self-assembling peptide RKP and found that it could be used to form excellent scaffolds for NP tissue engineering when mixed with RADA16-I at an equal volume ratio. However, BMP7 contains three different important short functional motifs, as above-mentioned.…”
Section: Introductionmentioning
confidence: 99%